Sodium tanshinone IIA sulfonate restrains fibrogenesis through induction of senescence in mice with induced deep endometriosis. Issue 3 (September 2020) - Luo, Min; Cai, Xianjun; Yan, Dingmin; Liu, Xishi; Guo, Sun-Wei
Highlights: Sodium tanshinone IIA sulfonate (STS) treatment stalled lesional development in a mouse model of deep endometriosis. It achieved its therapeutic effect seemingly through induction of cellular senescence. STS treatment also significantly reduced the plasma P-selectin and hyaluronic acid. STS appears to be a promising compound for treating endometriosis. Abstract: Research question: Does sodium tanshinone IIA sulfonate (STS) induce cellular senescence in endometriotic lesions and thus restrict lesional development and fibrogenesis in a recently established mouse model of deep endometriosis? Design: Prospective randomized animal experiment in which deep endometriosis was induced in female Balb/C mice, which were then randomly divided into three groups (low-dose STS, high-dose STS and inert vehicle control) and received treatment for 2 weeks. All mice were then sacrificed and their lesions excised and harvested. Lesion weight was quantified and all lesion samples were subjected to histochemical analysis of the extent of lesional fibrosis by Masson trichrome staining, and of cellular senescence by senescence-associated β-galactosidase (SA-β-gal), along with immunohistochemistry analyses of p53, CCN1, activate Salvador 1 (Sav1), hyaluronan synthase 2 (HAS2), survivin, granulocyte-macrophage colony-stimulating factor (GM-CSF) and CD163-positive M2 macrophages. Plasma P-selectin and hyaluronic acid levels were also quantified. Hotplate testing was also administered before the induction, then before and after treatment. Results: STS treatment resulted in significantly reduced lesion weight, stalled lesional fibrogenesis and improved hyperalgesia, seemingly through the induction of cellular senescence by activating p53, Sav1 and CCN1 while suppressing HAS2, survivin and GM-CSF, resulting in increased apoptosis and reduced lesional infiltration of alternatively activated macrophages. In addition, STS treatment significantly reduced the plasma concentration of P-selectin and hyaluronic acid, possibly leading to reduced lesional platelet aggregation. Conclusions: STS appears to be a promising compound for treating endometriosis. The results suggest that senescence may restrict lesional progression and fibrogenesis, and targeting the senescence pathway may have desirable therapeutic potential. Graphical abstract: Image, graphical abstract